155k views
5 votes
2x-1/3+3=x-3/5


pls do make sure to answer this *only if you know*
thank you

2 Answers

4 votes

Answer:

x = -
(49)/(15)

Explanation:

Given

2x -
(1)/(3) + 3 = x -
(3)/(5)

Multiply through by 15 ( the LCM of 3 and 5 ) to clear the fractions

30x - 5 + 45 = 15x - 9 , that is

30x + 40 = 15x - 9 ( subtract 15x from both sides )

15x + 40 = - 9 ( subtract 40 from both sides )

15x = - 49 ( divide both sides by 15 )

x = -
(49)/(15)

User CrafterKolyan
by
6.5k points
1 vote

Answer:


x = - 3 (4)/(15)

Explanation:


2x - (1)/(3) + 3 = x - (3)/(5)


= > 2x - ( 1 +9 )/(3) = x - (3)/(5)


= > 2x + (8)/(3) = x - (3)/(5)


= > 2x - x = - (3)/(5) - (8)/(3)


= > x = - (9 - 40)/(15)


= > x = - (49)/(15)


= > x = - 3 (4)/(15) (ans)

User EnaJ
by
5.7k points